Groups with weak maximality condition for nonnilpotent subgroups - Kurdachenko, L. A.; Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
A group G satisfies the weak maximality condition for nonnilpotent subgroups or, shortly, the condition Wmax-(non-nil), if Gdoes not possess the infinite ascending chains {H_n | n N} of nonnilpotent subgroups such that the indexes |H_n+i : H_n | are infinite for all n N. In the present paper, we study the structure of hypercentral groups satisfying the weak maximality condition for nonnilpotent subgroups.